Determinants of Labor Mobility with Spatial Approach System Literature Review (SLR) Method in Boyolali City, Indonesia - Tri Putri Kurniawati; Izza Mafruhah; Tetuko Rawidyo Putro (RIRAI Publisher, 2023)
The study includes the larges peer-reviewed database or labor economics. Sources of review literature are taken from the popular Google, namely Scopus, Emerald, and ScienceDirect. The PRISMA 2023 system for systematic review followed to the authors. 35 journals from the author's journals include in the collection. An interesting result is that the likelihood of side jobs, self-employment, and education level influence job shifts from the agricultural sector to other sectors. Authors with review literature are currently focused on Boyolali district, Central Java, Indonesia. In Boyolali district, Central Java, Indonesia, this is related to the reduction in labor from agricultural workers to other jobs. The author highlights in Boyolali district, Central Java, Indonesia, due to the influence of the pandemic era on more workers moving from agriculture to other sectors. Finally, Due to the level of training, business acumen, and the risk of an epidemic, it is evidence that work moves from the farm industry to other sectors. Due to the level of training, business acumen, and the risk of an epidemic, it is evidence that work moves from the farm industry to other sectors. This study uses a literature review on the movement of labor from the agricultural sector to other sectors through some data from central agencies and statistics, especially in Indonesia. The first systematic review of an increasingly relevant topic in the Boyolali district where the scope of work shifts has been a major point of expansion to other sectors.